Left atrial strain reduction in acute myocarditis and its association with incident atrial fibrillation. (4th February 2022) - Pastore, MC; Degiovanni, A; Spinoni, E; De Zan, G; Carassia, C; Patti, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The diagnostic and prognostic evaluation of acute myocarditis remains still challenging. Particularly, acute atrial involvement could be underdiagnosed due to its limited evaluation by cardiac magnetic resonance (CMR) and the lack of sensitive basic echocardiographic indices. Purpose: Our aim was to assess left atrial strain in a cohort of patients with diagnosis of acute myocarditis, and its correlation with incident cardiovascular events at follow up. Methods: 30 patients with acute myocarditis diagnosed by CMR, performed within one week from admission, according to Lake-Louise criteria were retrospectively included. Patients with poor acoustic window or missing data related to hospitalization or follow-up were excluded. Clinical characteristics, laboratory examinations, transthoracic echocardiography data were collected. Speckle tracking analysis was performed offline on the echocardiographic records. Follow up data were obtained via electronical records or phone-calls. Clinical endpoints were the development of all-cause or cardiovascular death, cardiovascular hospitalization (including heart failure, major arrhythmias, acute coronary syndromes), atrial fibrillation or ventricular arrhythmias onset. Results: The study cohort, composed of 30 patients with acute myocarditis (mean age 38 ±15 years, 33% (n = 10) female), showed raised C-reactive protein and cardiac troponin at admission, beside a mild reduction of left ventricular ejection fraction (Fig.1). Left ventricular strain was preserved in the majority of patients (57%, n = 17) or mildly reduced, while left atrial strain was significantly reduced (Table 1). At CMR, 57% (n = 17) of patients presented myocardial edema and 70% (n = 21) presented late gadolinium enhancement.  Over a mean follow up of 2.3 ± 1.9 years, 5 patients had hospitalizations for cardiovascular reasons, one of whom for heart failure, 3 patients developed atrial fibrillation, 5 patients developed ventricular arrhythmias. Patients with cardiovascular events showed lower left atrial strain than those without events (Fig.2); global atrial reservoir strain reached a statistically significant difference in patients with incident atrial fibrillation vs those without (p = 0.02). Conclusions: our findings suggest that patients with acute myocarditis may have a subtle atrial involvement which could be detected by speckle tracking echocardiography. Moreover, lower values of left atrial strain may characterize patients at higher risk of incident atrial fibrillation during follow-up.